Pengaruh Tambang Emas Gunung Botak Terhadap Perilaku Masyarakat di Desa Dava Kabupaten Buru - Rusdi, M.; P, Reski; Hajar, Ibnu; Ismail, Ismail; Papuangan, Astriyani A. (ETHNOGRAPHY: Journal of Design, Social Sciences and Humanistic Studies, 2025)
This research aims to describe the influence of mining on behavioral changes and to identify the factors affecting the emergence of social and economic behavioral changes in the community. This type of research is qualitative descriptive. Informants are determined through purposive sampling, where the researcher intentionally selects based on predetermined criteria set according to the research objectives. Data is collected through observations, interviews, and documentation. Data analysis is conducted through the stages of data reduction, data presentation, verification, and conclusion drawing. The results of this study explain that the impact of mining on community behavior is that socially, there has been a significant change in the social structure, tensions, and conflicts due to role shifts and injustices in the distribution of mining profits, which trigger polarization, mistrust, changes in communication patterns, as well as increased violence and aggression. Economically, the community experiences changes in livelihoods, with many transitioning to become miners, and an increase in income that affects changes in consumption patterns, lifestyles, and social status symbols. Factors influencing the emergence of the socio-economic behavior of communities around mining include the economic impact of mining, migration and urbanization, environmental impacts, and cultural and value influences.